Longitudinal increases in reward-related neural activity in early adolescence: Evidence from event-related potentials (ERPs) - Burani, Kreshnik (Dev Cogn Neurosci, 2019)
Adolescence is frequently described as a developmental period characterized by increased sensitivity to rewards. However, previous research on age-related changes in the neural response to gains and losses have produced mixed results, with only some studies reporting potentiated neural responses during adolescence. The current study examined the ERP responses to gains and losses during a simple monetary reward (i.e., Doors) task in a large and longitudinal sample of 248 adolescent females assessed at two time points, separated by two years. At baseline, when the sample was 8- to 14-years-old, age related to larger (i.e., more positive) ERP responses to both gains and losses; moreover, age-related effects were stronger in relation to gains than losses. Overall, the amplitude of the ERP response to gains, but not losses, significantly increased from baseline to follow-up; however, this effect was moderated by age, such that reward-related ERPs only increased longitudinally among the younger participants. At the follow-up assessment, ERP responses to gains and losses were equally related to age. Collectively, these within- and between-subjects findings suggest a relatively specific developmental increase in reward-related neural activity during late childhood and early adolescence.